HUBUNGAN JUMLAH FOLIKEL ANTRAL DENGAN RESPONS OVARIUM TERHADAP STIMULASI OVULASI - Adnyana, IB Putra (journal of internal medicine, 2006)
Recent studies show there is possibility to predict ovarian response to ovulation stimulation. Several possiblepredictor factors are age, ovarian volume, antral follicle count (AFC), ovarian stroma blood flow, and hormonalmarkers like Follicle Stimulating Hormone (FSH), Estradiol (E2) and Inhibin B. AFC is a simple examination forovarian reserve. Compared with hormonal markers, AFC more simply, relatively less costly and only using ultrasoundmachine, which widely available and the result could be obtained in timely manner. To understand relationshipbetween AFC and ovulation stimulation response. All women who joined IVF program with short protocol stimulationfrom January 2005 until May 2006 were enrolled into the study. Data collected were AFC day two, mature folliclecount, total oocyte count, mature oocyte count, and total gonadotrophin dose. Data were analyzed with Kendall’scorrelation test to show relationship. This study shows statistically significant correlations between AFC with maturefollicle count (r=0,329; p=0,037), total oocyte count (r=0,506; p=0,001), mature oocyte count (r=0,492; p=0,002), andtotal gonadotrophin dose (r=-0,477; p=0,002). This study shows there are statistically significant correlations betweenAFC with ovarian response to ovulation stimulation and the cutoff point of AFC is 4,5.